Pyrolysis assessment of palm kernel shell waste valorization to sulfonated magnetic biochar from techno-economic and energy perspectives - Seow, Yee Xuan; Tan, Yie Hua; Jibrail, Kansedo; Tan, Inn Shi; Chin, Bridgid Lai Fui; Nabisab Mujawar, Mubarak; Mohd Nurfirdaus, Mohiddin; Peter Nai Yuh, Yek; Chan, Yen San; Mohammad Omar, Abdullah (Springer Nature Switzerland AG, 2024)
Most agricultural activities generate a significant quantity of biomass waste that has not been fully utilized. This study utilized palm kernel shells as the primary material to produce sulfonated magnetic palm kernel shell biochar. The post-sulfonation magnetic palm kernel shell biochar had a greater particle size of around 137 nm compared to the pre-sulfonation biochar. This increase in size can be attributed to the presence of the − SO3H group. The biochar that underwent post-sulfonation was chosen for a techno-economic evaluation to ascertain its viability in terms of economics and energy efficiency. Soybean straw and coconut shell-derived biochar were chosen for the techno-economic assessment. The energy intake for soybean straws, coconut shells, and palm kernel shells derived from biochar is 48.85 MJ∙kg−1, 23.83 MJ∙kg−1, and 52.44 MJ∙kg−1, respectively. The energy output for soybean straws, coconut shells, and palm kernel shells derived biochar is determined to be 22.54 MJ∙kg−1, 23.68 MJ∙kg−1, and 31.55 MJ∙kg−1, respectively. The ultimate profit-to-cost ratios of soybean straws, coconut shells, and palm kernel shells derived biochar are 0.21, 4.92, and 1.11, respectively. The techno-economic assessment indicates that coconut shell-derived biochar production is favourable, primarily due to its attributes of low net energy balance, high porosity, and lower density. Both coconut shells and palm kernel shells derived biochar productions are economically viable and efficient due to their high profit-to-cost ratio. The microwave-assisted technology is proven efficient and demands less energy to generate an equivalent quantity of biochar compared to traditional furnaces.